1999
DOI: 10.1126/science.283.5405.1138
|View full text |Cite
|
Sign up to set email alerts
|

Magma Flow Instability and Cyclic Activity at Soufriere Hills Volcano, Montserrat, British West Indies

Abstract: Dome growth at the Soufriere Hills volcano (1996 to 1998) was frequently accompanied by repetitive cycles of earthquakes, ground deformation, degassing, and explosive eruptions. The cycles reflected unsteady conduit flow of volatile-charged magma resulting from gas exsolution, rheological stiffening, and pressurization. The cycles, over hours to days, initiated when degassed stiff magma retarded flow in the upper conduit. Conduit pressure built with gas exsolution, causing shallow seismicity and edifice inflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
239
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(259 citation statements)
references
References 12 publications
19
239
1
Order By: Relevance
“…Page | 17 monitored in unprecedented detail, with timing, volume and flow dynamic data all recorded for individual pyroclastic flows Barclay et al, 1998;Sparks et al, 1998Sparks et al, , 2000Young et al, 1998;Cole et al, 1998;Menlik and Sparks, 1999;Voight et al 1999;Couch et al, 2001Couch et al, , 2003Zellmer et al, 2003;Herd et al, 2005). In addition, the combined study of subaerial flow conditions into the ocean with in-situ deposit morphology derived from marine sediment cores during the current eruption has provided valuable insights into submarine pyroclastic flow emplacement dynamics (Trofimovs et al, 2006(Trofimovs et al, , 2008(Trofimovs et al, , 2013Le Friant et al, 2009.…”
Section: Montserrat: the Natural Laboratorymentioning
confidence: 99%
“…Page | 17 monitored in unprecedented detail, with timing, volume and flow dynamic data all recorded for individual pyroclastic flows Barclay et al, 1998;Sparks et al, 1998Sparks et al, , 2000Young et al, 1998;Cole et al, 1998;Menlik and Sparks, 1999;Voight et al 1999;Couch et al, 2001Couch et al, , 2003Zellmer et al, 2003;Herd et al, 2005). In addition, the combined study of subaerial flow conditions into the ocean with in-situ deposit morphology derived from marine sediment cores during the current eruption has provided valuable insights into submarine pyroclastic flow emplacement dynamics (Trofimovs et al, 2006(Trofimovs et al, , 2008(Trofimovs et al, , 2013Le Friant et al, 2009.…”
Section: Montserrat: the Natural Laboratorymentioning
confidence: 99%
“…Examples include Mount St. Helens in the 1980s, where tiltmeters were used to predict effusive eruptions [Dzurisin et al, 1983], and Soufriere Hills Volcano (Montserrat), where tiltmeters revealed remarkable cyclic eruptive activity correlated with seismicity, gas emissions, explosions, and pyroclastic flows [Voight et al, 1998;Watson et al, 2000] and helped place constraints on source processes and boundary conditions on the conduit walls [Green et al, 2006;Widiwijayanti et al, 2005;Voight et al, 1999;Lensky et al, 2008]. Cyclic or repeating behavior on a variety of timescales has also been observed with different types of instruments during other silicic eruptions including Mount St. Helens during the 2004-2008 eruption [Iverson et al, 2006], Pinatubo [Mori et al, 1996], Santiaguito [Bluth and Rose, 2004], and Unzen [Nakada et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…The extracted event data were processed further to determine accurate rst Hybrid swarms of shallow origin at SHV were recognized within pressurization 219 cycles, with swarms occurring during in ation when extrusion rates are low 220 and the system is pressurized (Voight et al, 1998(Voight et al, , 1999Sparks and Young, low extrusion rates and in ation as seen in 1997 (Voight et al, 1998). Con- Chouet, B., 1996a.…”
mentioning
confidence: 99%